Highly efficient hamburger-like nanostructure of a triadic Ag/Co3O4/BiVO4 photoanode for enhanced photoelectrochemical water oxidation. Issue 73 (21st December 2020) - Gao, Xintong; Bai, Zhiqun; Zhang, Shuai; Liu, Jingchao; Li, Zenghe
Abstract : A novel hamburger-like nanostructure of a triadic photoanode Ag/Co3 O4 /BiVO4 was designed to enhance photoelectrochemical water splitting, providing a fascinating pathway to efficiently improve the PEC conversion efficiency. Abstract : The combination of a semiconductor heterojunction and oxygen evolution cocatalyst (OEC) is an important strategy to improve photoelectrochemical (PEC) water oxidation. Herein, a novel hamburger-like nanostructure of a triadic photoanode composed of BiVO4 nanobulks, Co3 O4 nanosheets and Ag nanoparticles (NPs), that is, Ag/Co3 O4 /BiVO4, was designed. In our study, an interlaced 2D ultrathin p-type Co3 O4 OEC layer was introduced onto n-type BiVO4 to form a p–n Co3 O4 /BiVO4 heterojunction with an internal electric field (IEF) in order to facilitate charge transport. Then the modification with Ag NPs can significantly facilitate the separation and transport of photogenerated carriers through the surface plasma resonance (SPR) effect, inhibiting the electron–hole recombination. The resulting Ag/Co3 O4 /BiVO4 photoanodes exhibit largely enhanced PEC water oxidation performance: the photocurrent density of the ternary photoanode reaches up to 1.84 mA cm −2 at 1.23 V vs. RHE, which is 4.60 times higher than that of the pristine BiVO4 photoanode. The IPCE value is 2.83 times higher than that of the pristine BiVO4 at 400 nm and the onset potential has a significant cathodic shift of 550 mV for the ternary well-constructed photoanode.